Assessment of Knowledge, Attitude and Practice of Undergraduate Final Year Dental Students and House Officers Regarding Radiation Protection Protocols: A Question Based Cross-Sectional Study (Medical Forum Monthly, 2023)
Objective: To assess the prevalence and causes of renal disorders in patients undergoing renal biopsies, with a focus on assessing the safety and adequacy of the biopsy procedure.Study Design: A cross-sectional studyPlace and Duration of Study: This study was conducted at the Nephrology Department of Central Park Teaching Hospital, Lahore in collaboration with Department of Nephrology, Choudhary Muhammad Akram Teaching Hospital, Lahore from December 2022 to June 2023.Methods: Seventy-eight participants aged 15 to 60 years, undergoing renal biopsy for definitive diagnosis, were recruited after obtaining prior written informed consent. Sociodemographic details, medical history, and biopsy-related information were recorded. Renal biopsies were assessed for safety and adequacy, including pre- and post-biopsy hemoglobin levels. Statistical analysis was performed using SPSS version 26.0.Results: The study population comprised 64.1% females, with 10.25% being hypertensive and 5.12% diabetic. Renal biopsies were deemed safe, with a mean glomeruli count of 19.49 and minimal blood loss (mean difference: 0.79 mg/dL). Lupus nephritis (30.8%) and nephrotic syndrome (12.80%) were major reasons for biopsies, with various other causes identified. Biopsy-proven diagnoses included focal segmental glomerulosclerosis, membranous glomerulonephritis, and lupus nephritis of varying classes.Conclusion: This study underscores the importance of renal biopsies in diagnosing CKD and guiding treatment, with a focus on safety and adequacy of the procedure. Prevalent causes of CKD included autoimmune conditions such as lupus nephritis and nephrotic syndrome